OBSERVATIONS ON GROWTH AND MOULTING OF SPINY LOBSTERS PANULIRUS HOMARUS (LINNAEUS), P. ORNATUS (FABRICIUS) AND P. PENICILLATUS (OLIVIER) IN CAPTIVITY - Nair, R V; Soundararajan, R V; Nandakumar, G (Indian Journal of Fisheries, 2011)
The growth and moulting of three species of Panulirlls, ’:lamely Panlllirus fwmarus (Linnaeus), Panlllirus ornatllS (Fabricius) ’nd Panlllirlls penicillatus (Olivier) in captivity have been studied. The average growth ioorement per moult was 2.3-3.4 mm carapace length (6.9-9.6 mm total length) for male and 2.3 3.() mm C.L (6.5-9,1 rom T.L.) for fema[e P. homarus, 2.7 mm c.L. (1’1.3 mm T.L.) for male and 3.3-4.4 mm C.L (IH.S .. 13.,S mm TL.) for female P. ornatus and 1.5 mm C.L. (5.5 mm T.L.) for male P. penicillatus. The gmwth mtÂ·e has been found to be higher in younger individuals than in older ones. P. homarus moulted eight times in about fifteen months, P. ornatus moulted seven times and P. penicillatlls sil)( times- in albout twe’:1tycme months. An instance of breeding in captivity i" P. homarus is reported. The prOISpects for culturing !obstÂ·e,rs in M-andapam area are inill’cated.